Salazar, Noel B. i Graburn, Nelson H. H. (eds.) (2014). Tourism imaginaries. Anthropological approaches - Josep Maria Prat Forga (Documents d'Anàlisi Geogràfica, 2015)
Salazar, Noel B. i Graburn, Nelson H. H. (eds.) (2014) Tourism imaginaries. Anthropological approaches Oxford: Berghahn Books, 304 p. ISBN 978-1-78238-367-3